Analisis Perencanaan Laba pada Usaha Mikro Kecil Menengah - Pamungkas, Eko Wiji; Sumiati, Sumiati (TECHNO-SOCIO EKONOMIKA, 2026)
This study aims to analyze the application of Break-Even Point (BEP) and Margin of Safety (MoS) as profit planning instruments in small and medium enterprises (SMEs) engaged in Nile tilapia aquaculture in Purwakarta Regency. The research employs a qualitative descriptive method with a case study approach, utilizing data collected through interviews, observations, and documentation. The data are subsequently analyzed using BEP and MoS calculations The findings indicate that the business has reached its break-even point and demonstrates a relatively high margin of safety, suggesting that it remains in a secure condition despite potential declines in revenue. These results confirm that BEP and MoS analyses are effective strategies for profit planning, as they assist business actors in determining sales targets, controlling costs, and anticipating market uncertainties.Furthermore, the implementation of simple yet strategic financial analysis is essential to enhance operational efficiency, maintain business stability, and strengthen the sustainable competitiveness of SMEs.